Isolasi dan Uji Aktivitas Enzim Selulase dari Bakteri Simbion Larva Kupu-Kupu Family: Cossidae Terhadap Variasi Lama Inkubasi - Dwismar, Rina; Baharuddin, Maswati; HS, Syamsidar (Al-Kimia, 2013)
The study is titled Isolation and Testing Cellulase Enzymes from Bacterial Symbiont butterfly larvae Family: Cossidae of Variations on Old Incubation aimed to isolate cellulase enzymes in larvae of butterflies and determine tIsolasi dan Uji Aktivitas Enzim Selulase dari Bakteri Simbion Larva Kupu-Kupu Family: Cossihe optimum incubation time of enzyme production and activity of enzymes to degrade CMC substrate. In this study, an enzyme produced from the microbial gut symbionts Cossidae butterfly larvae that had been cultured in media cellulolytic, then produced the long incubation variation of 0, 12, 24, 36, 48, 60, and 72 hours, crude enzyme obtained by centrifugation at a speed of 5000 rpm at 40C and then tested enzyme activity using UV-VIS spectrophotometer. From the research result that cellulolytic bacteria can be isolated from the gut of larvae of butterlies Family: Cossidae with old optimum activity of cellulase enzyme production is 60 hours with a value of activity amounted to 2,38 x 10-3 U/mL.